Analisis Longitudinal Struktur Komunitas Makrozoobentos yang Tercemar Limbah Pertambangan Emas Skala Kecil di Sungai Cikondang, Jawa Barat - Kabul Fadilah; Tika Nurmala; Tri Dewi K.P.; Yayok Suryo Purnomo; Sunardi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Small-scale gold mining activities are still mostly carried out in various regions in Indonesia. The use of mercury (Hg) in the process of extracting gold from sediments can be a source of pollution for aquatic ecosystems and organisms. The aim of this study was to analyze the macrozoobenthos community structure in the Cikondang River which was affected by Hg pollution due to small-scale gold mining. Sampling was carried out by survey method at 5 sampling points along the Cikondang River from upstream to downstream. Water quality parameters measured include temperature, transparency, current velocity, pH, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). Hg concentrations in sediments and macrozoobenthos were measured using automatic mercury analyzer. The results showed that the concentration of Hg in sediments in the Cikondang River ranged from 0.63–52.48 mg/kg and the accumulation of Hg in macrozoobenthos ranged from 0.97 to 0.98. The macrozoobenthos diversity index was 1.50-2.17 and the dominance index was 0.16-0.30. The most group of macrozoobenthos found was from the Gastropod class, followed by the Insecta and Malacostraca classes. Macrozoobenthos in the Cikondang River were only found in the downstream of the river, at Sampling Points 4 and 5 only. This showed that Hg pollution in the Cikondang river is highly toxic, caused macrozoobenthos was not found at Sampling Point 1, 2 and 3.